How has the initial lockdown and reopening due to the COVID-19 pandemic affected physical activity level and well-being in Turkey? - Soysal Tomruk, Melda; Tomruk, Murat; Çalık, İsmail (Journal of Surgery and Medicine, 2022)
Background/Aim: The worldwide spread of COVID-19 caused changes in daily routines. During the lockdown, parks and gyms were closed and access to outdoor areas was limited. After reopening, many restrictions were removed. Since this process may have altered physical activity and well-being levels, this study aimed to explore how physical activity (PA) levels and well-being of Turkish citizens were affected by the initial COVID-19 lockdown and the reopening. Methods: In this prospective, cross-sectional study, participants were asked to complete an online survey twice: first in May 2020 (when initial strictest partial lockdown procedures were applied) and second in July 2020 (after most restrictions had been removed). The online survey consisted of questions related to demographics, PA levels, and well-being. Categorical questions (expressed as either day per week or min per day) were used to assess vigorous and moderate PA, time spent sitting, etc. The WHO-5 Well-Being Index was used to assess well-being. Results: The mean age and the body mass indexes of 94 individuals (52 females, 42 males) were 36.16 (10.04) years and 25.14 (3.82) kg/m2, respectively. During both lockdown and after reopening, low levels of PA and well-being levels above the low mood limit (< 50) were identified. No significant change was found in either any of the PA-related variables or the well-being of participants between the initial and final assessments (P > 0.05). Conclusion: Our results showed that PA levels and well-being of Turkish citizens remained unchanged after the reopening process when compared to the initial lockdown due to COVID-19. These findings may also suggest that reopening was not a sufficient stimulant factor to alter physical activity and well-being. Despite all the negative effects brought on by the pandemic, it is essential to adopt approaches to keep PA levels and well-being high.